2019
DOI: 10.14254/2071-789x.2019/12-3/17
|View full text |Cite
|
Sign up to set email alerts
|

Governance codes in the developing and emerging countries: Do they look for the international role model?

Abstract: Over the last decade, a growing number of developing and emerging countries have begun addressing corporate governance practice and issued a national governance code. This paper analyses and compares the code contents and approaches of the 11 developing and emerging countries after the latest revision of the OECD Principles of Corporate Governance to examine whether these countries follow the international best practice despite the national specifics differ from those of developed countries. Individual codes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
7
0
3
Order By: Relevance
“…As propostas do citado relatório buscaram, sobretudo, contribuir positivamente para a promoção das boas práticas de GC (Oyarzún, 2011). Isto é, o Relatório Cadbury (1992) forneceu o legado de definição de GC como o sistema pelo qual as empresas são dirigidas e controladas, como também a adoção voluntária das melhores práticas de governança baseada no princípio "cumprir ou explicar" (Shah & Napier, 2017;Bosáková, Kubíček & Strouhal, 2019).…”
Section: Cadbury Reportunclassified
See 2 more Smart Citations
“…As propostas do citado relatório buscaram, sobretudo, contribuir positivamente para a promoção das boas práticas de GC (Oyarzún, 2011). Isto é, o Relatório Cadbury (1992) forneceu o legado de definição de GC como o sistema pelo qual as empresas são dirigidas e controladas, como também a adoção voluntária das melhores práticas de governança baseada no princípio "cumprir ou explicar" (Shah & Napier, 2017;Bosáková, Kubíček & Strouhal, 2019).…”
Section: Cadbury Reportunclassified
“…Ribeiro / Desafio Online v.11, n.2, art.6 Mai./Ago. (2023) [315][316][317][318][319][320][321][322][323][324][325][326][327][328][329][330][331][332][333] literatura científica internacional, o Relatório Cadbury permanece sendo um dos alicerces e nortes para pesquisas científicas que envolvam as boas práticas de governança corporativa no mundo (Oyarzún, 2011;Shah & Napier, 2017;Bosáková, Kubíček & Strouhal, 2019).…”
Section: Redes Sociais Two-mode Dos Períodos E Dos Artigosunclassified
See 1 more Smart Citation
“…Such barriers, in their turn, can be generated by inefficient public administration and essential share of informal economy (Mishchuk et al, 2020), which is a ubiquitous obstacle for development in entrepreneurial environment. To mitigate this and other barriers in entrepreneurial surrounding, some countries started to implement the best governance practice and issued national governance codes (Bosáková et al, 2019). Pavlák (2018) defined the major obstacles in the case of Czech SMEs as high costs of internationalisation, administrative obstacles, lack of information about foreign markets, and insufficient capital for expansion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because as per Claessens ( (Claessens 2006)), lack of understanding could be a factor in the proper implementation of corporate governance reforms. Bosakova et al ( (Bosáková et al 2019)) concluded in a recent study that the "comply or explain" approach is inadequate in the emerging countries context and recommended a stricter approach to ensure compliance with the national Corporate Governance Code.…”
Section: Straighten the Implementation And Enforcement Of The Regulationsmentioning
confidence: 99%